The transition between work, sickness absence and pension in a cohort of Danish colorectal cancer survivors - Carlsen, Kathrine (BMJ Publishing Group, 2013)
OBJECTIVES: The aim of this study was to evaluate the impact of socioeconomic and clinical factors on the transitions between work, sickness absence and retirement in a cohort of Danish colorectal cancer survivors. DESIGN: Register-based cohort study with up to 10 years of follow-up. SETTING: Population-based study with use of administrative health-related and socioeconomic registers. PARTICIPANTS: All persons (N=4343) diagnosed with colorectal cancer in Denmark during the years 2001–2009 while they were in their working age (18–63 years) and who were part of the labour force 1 year postdiagnosis. PRIMARY AND SECONDARY OUTCOME MEASURES: By the use of multistate models in Cox proportional hazards models, we analysed the HR for re-employment, sickness absence and retirement in models including clinical as well as health-related variables. RESULTS: 1 year after diagnosis, 62% were working and 58% continued until the end of follow-up. Socioeconomic factors were found to be associated with retirement but not with sickness absence and return to work. The risk for transition from work to sickness absence increased if the disease was diagnosed at a later stage (stage III) 1.52 (95% CI 1.21 to 1.91), not operated curatively 1.35 (95% CI 1.11 to 1.63) and with occurrence of postoperative complications 1.25 (95% CI 1.11 to 1.41). The opposite was found for the transition from sickness absence back to work. CONCLUSIONS: This nationwide study of colorectal cancer patients who have survived 1 year shows that the stage of disease, general health condition of the individual, postoperative complications and the history of sickness absence and unemployment have an impact on the transition between work, sickness absence and disability pension. This leads to an increased focus on the rehabilitation process for the more vulnerable persons who have a combination of severe disease and a history of work-related problems with episodes outside the working market.